(untitled) - Franek, F. (Cambridge,New York, 2004)
The overwhelming majority of bugs and crashes in computer programming stem from problems of memory access, allocation, or deallocation. Such memory related errors are also notoriously difficult to debug. But the role that memory plays in C and C++ programming is a subject often overlooked in courses and in books. Most professional programmers learn about it entirely through experience of the trouble it causes. This book provides students and professional programmers with a concise yet comprehensive view of the role memory plays in all aspects of programming and program behaviour. Assuming only a basic familiarity with C or C++, the author describes the techniques, methods, and tools available to deal with the problems related to memory and its effective use
Keywords: Memory management (Computer science),C (Computer program language),C++ (Computer program language),Quản lý bộ nhớ (Khoa học máy tính),C++ (Ngôn ngữ lập trình máy tính),C (Ngôn ngữ lập trình máy tính)